The Process and Challenges of International Academic Collaboration in STEM - Badhrulhisham, Abdul Aziz; Daing Nasir, Ibrahim; Gharayeb, O.; Ibrahim, A. (2015)
At the end of presentation, participants will be able to: view STEM in Malaysia, value the benefits of international academic collaboration, apply various activities in international academic collaboration, experience the challenges faced during the collaboration process.